Persepsi label halal pada makanan impor halal berdasarkan faktor pekerjaan Konsumen di Indonesia - Ratna Ratna (Politeknik Negeri Bandung, 2018)
Islam is a growing religion with a high number of adherents including in Indonesia. Islam organizes all activitiesin various sectors such as social, educational, economic, political, behavioral, also the selection of foods thatshould be halal. Halal does not contain ingredients or elements that are prohibited to be consumed and processedbased on Islamic sharia. The increasing number of imports in Indonesia is high enough to affect the expand numberof products from foreign countries where producers come from non-Muslim countries. Similarly, there is a boostin consumer awareness of Indonesia to halal products which is the impact of the appearance of products labeledhalal fake cases. The aim of the study is to measure the perception of halal label based on work profile in Indonesia.This study used quantitative data through questionnaires with 8 statements to 411 Muslim respondents who everconsume halal imported food through random sampling. The data obtained were analyzed using SPSS version 18with chi square and description methods. The research findings show that there is no relationship betweenoccupation toward perception of halal label on halal impor food and each occupational groups have the differentsight. Furthermore, in general consumers have high considerable attention on halal labels in imported products.